2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Child Labor [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS, 2003)
Child labor regulations provides federal standards for the employment of children (minors) in agriculture. This is EDIS document FE391, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.